The Acceptability of Religious Terms Translation in the Complete Idiot’s Guide to Understanding Islam - Nadia Gitya Yulianita; Mangatur Nababan; Djatmika Djatmika (Bina Nusantara University, 2018)
This research aimed to find out the used translation’s techniques and the acceptability of the translation. This was a descriptive qualitative research and an embedded-case study. Based on semantic and relevance theory, the researcher determined good translation. This research was conducted by listing the religious terms found in The Complete Idiot’s Guide to Understanding Islam. Then, the researchers compared the source language and target language to identify the translation techniques. Finally, the researchers and raters assessed the acceptability of the translation by conducting Focus Group Discussion (FGD). The result shows that the translator uses established equivalent, borrowing, literal, particularization, generalization, transposition, reduction, addition, explication, and discursive creation. Besides, the average rate for the acceptability of the translation is 2,8 out of 3. It means that the translation is mostly in accordance with the norm and rule of language in the target text.